Desmoid tumours in the surveillance era: What are the remaining indications for surgery?. Issue 7 (July 2020) - Improta, Luca; Tzanis, Dimitri; Bouhadiba, Toufik; Abdelhafidh, Khoubeyb; Bonvalot, Sylvie
Abstract: The treatment of desmoid tumours (DTs) has greatly evolved in recent years, and surgery is no longer considered a first-line treatment. Percutaneous biopsy with molecular analysis for beta-catenin or APC gene mutation provides a certain diagnosis. After imaging, a specialized multidisciplinary tumour board (MDT) addresses the following therapeutic strategy. As more than half of patients stabilize or regress, despite initial progression, active surveillance is offered to most patients as the first option. Surgery is proposed for complications such as perforation and occlusion, which sometimes are the first manifestations of the disease. In these cases, limiting surgery to the treatment of complications and leaving the tumour in place is possible if significant bowel sacrifice is needed, especially in patients with previous colectomy for polyposis. Medical therapy is discussed by the MDT in cases of functional or life-threatening masses and is preferred to local treatments that could be mutilating and often incomplete. First-line surgery is now contraindicated in cases of incomplete unplanned surgery, recurrence, pregnancy or DTs occurring in familial adenomatous polyposis (FAP). The best indications of second-line surgery are significantly progressing disease when morbidity is acceptable, such as parietal locations. Medical and other locoregional treatments (radiotherapy, isolated limb perfusion and cryotherapy) should be considered by the MTB when surgery might cause sequelae.